2009
DOI: 10.1186/1479-5876-7-109
|View full text |Cite
|
Sign up to set email alerts
|

Short-term cultured, interleukin-15 differentiated dendritic cells have potent immunostimulatory properties

Abstract: BackgroundOptimization of the current dendritic cell (DC) culture protocol in order to promote the therapeutic efficacy of DC-based immunotherapy is warranted. Alternative differentiation of monocyte-derived DCs using granulocyte macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-15 has been propagated as an attractive strategy in that regard. The applicability of these so-called IL-15 DCs has not yet been firmly established. We therefore developed a novel pre-clinical approach for the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 56 publications
(91 reference statements)
3
109
0
2
Order By: Relevance
“…68 Hence, the presence of CD4 þ T-cell 'helper' epitopes within the larger structure of the antigen is a highly desirable immunogenic property. 69 Antigenic peptides presented by MHC class II molecules are usually longer than peptide fragments bound to MHC class I molecules, the latter typically being nine amino acids in length (nonapeptides).…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Hence, the presence of CD4 þ T-cell 'helper' epitopes within the larger structure of the antigen is a highly desirable immunogenic property. 69 Antigenic peptides presented by MHC class II molecules are usually longer than peptide fragments bound to MHC class I molecules, the latter typically being nine amino acids in length (nonapeptides).…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 99%
“…25 CD8 þ T cells specific for G250/CAIX [24][25][26][27][28][29][30][31][32] , G250/CAIX 254-262 and RHAMM [165][166][167][168][169][170][171][172][173] are also regularly detected in the peripheral blood of AML patients, with frequencies of 60%, 13% and 47%, respectively. 25 In a series of 15 AML patients, Siegel et al 22 observed spontaneous T-cell immune responses to different HLA-A*0201-restricted T-cell epitopes derived from OFA-iLRP, including iLR1 [59][60][61][62][63][64][65][66][67][68] (6/15) …”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 99%
“…49 These data could support the implementation of IL-15 expressing DCs into clinical trials. [54][55][56][57] Impact of DCs on effector functions of gd T cells The two main effector functions of gd T cells which would be desirable in the context of cancer immunotherapy are a direct cytotoxicity toward tumor cells and an immunomodulatory function through the secretion of pro-inflammatory cytokines including IFN-g and TNF-a.…”
Section: Dc-mediated Gd T Cell Proliferationmentioning
confidence: 99%
“…These are also high on the list of priorities, as MoDC cultured in GM-CSF 1IL-15 are superior in vitro in inducing high-affinity CTL [79,80]. It remains difficult for us to generate a sufficient number of highly standardized DC under these conditions, which is a prerequisite for true GMP production.…”
Section: Modc Generated Using Gm-csf1 Il-15mentioning
confidence: 99%